Enantioseparation of new axially chiral carboxylic acids on polysaccharide-based chiral stationary phases under normal phase elution conditions - Barbara Sechi; Victor Mamane; Roberto Dallocchio; Alessandro Dessì; Sergio Cossu; Giorgi Jibuti; Paola Peluso (Journal of Pharmaceutical and Biomedical Analysis Open)
In the last decade, the availability of new and versatile synthetic strategies for the preparation of substituted 4,4’-bipyridyl derivatives based on chemo- and regioselective functionalization of the 4,4’-bipyridine core has encouraged studies for exploring the bioactivity of these compounds in the fields of drug discovery and medicinal chemistry. In substituted 4,4’-bipyridines, chirality may emerge from restricted rotation induced by sterically hindered atoms or functional groups located around the 4,4’-biaryl bond (chiral axis). The first atropisomeric substituted 4,4’-bipyridine was prepared in 2008, and no asymmetric synthesis to produce pure atropisomers of chiral 4,4’-bipyridine derivatives has been available so far. Thus, in the last few years, our groups developed methods to separate atropisomers of a wide series of 4,4’-derivatives by high-performance liquid chromatography (HPLC) using polysaccharide-based chiral stationary phases (CSPs). In the frame of our interest in this field, we reported herein the synthesis of two new chiral carboxylic acids containing an axially chiral 4,4’-bipyridyl unit as source of chirality, and their HPLC enantioseparation on polysaccharide-based CSPs. In particular, the impact of analyte and CSP structures on the enantioseparation outcomes as well as mechanisms and noncovalent interactions underlying the enantioseparation were explored by using electrostatic potential analysis and molecular dynamics (MD) simulations.